WITH CRAFT SPONSORS RELATED UDUMS - Esonov Ziyodbek Yuldashevich (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, Fergana Valley craftspeople’s activities related to patrons of crafts are highlighted. The main focus is on the patron symbols preserved in Ferghana Valley handicrafts and the customs associated with them, showing that they have changed under the influence of Islam.